Mortality in northern corroboree frog tadpoles (Pseudophryne pengilleyi) associated with Tetrahymena‐like infection. Issue 8 (August 2015) - Holz, PH; Portas, T; Donahoe, S; Crameri, S; Rose, K
<x xml:space="preserve">Abstract</x> Case report Mortality of northern corroboree frog tadpoles and eggs occurred in association with Tetrahymena‐like ciliates. The predominant lesions in the tadpoles were inflammation and necrosis of the dermis and skeletal muscle. Some of the egg capsules also contained ciliates, but were overgrown with bacteria and fungi. Conclusion Disease occurred, secondary to underlying husbandry issues, and resolved following their correction.